Penelitian Sastra Pemaknaan Heuristik, Hermeneutik, dan Kritik Sosial dalam Kumpulan Puisi Pahlawan dan Tikus Karya A. Mustofa Bisri: Kajian Semiotika - Hasmiyatni, Dwi Meilani; Herlina, Lina; Anwar, Rivaldi (Suara Bahasa, 2024)
This research examines the meaning of heuristics, hermeneutics and social criticism in the book A Collection of Poems on Heroes and Mouse by A. Mustofa Bisri, using a qualitative descriptive method with Michael Riffaterre's semiotic approach. The research data comes from heuristic and hermeneutic analysis of six poems in this book, namely "Sun Red Padam," "Earth is Confused," "When God," "Forward Undaunted," "Heroes," and "Rats." Research findings show that each poem contains deep meaning related to themes of humanity, social justice and struggle. The poem "When God" highlights the complexity of humans as caliphs on earth, describing the potential for good and bad that angels do not fully understand. The poems "Rats" and "Bumi Confused" criticize greed and environmental damage caused by humans. Meanwhile, “Forward Without Fear” and “Heroes” emphasize the importance of courage in fighting injustice. Ultimately, “Sun Merah Padam” reflects suffering and disappointment but still radiates hope for change. The results of this research enrich understanding of the relevance of social and humanitarian criticism in poetry, as well as the importance of heuristic and hermeneutic aspects in understanding the layers of meaning within it